Associations of dietary folate, Vitamins B6 and B12 and methionine intake with risk of breast cancer among African American and European American women. Issue 6 (30th September 2013) - Gong, Zhihong; Ambrosone, Christine B.; McCann, Susan E.; Zirpoli, Gary; Chandran, Urmila; Hong, Chi‐Chen; Bovbjerg, Dana H.; Jandorf, Lina; Ciupak, Gregory; Pawlish, Karen; Lu, Quanjun; Hwang, Helena; et al.
<x xml:space="preserve">Abstract</x> African American (AA) women are more likely than European American (EA) women to be diagnosed with breast cancer at younger ages and to develop poor prognosis tumors. However, these racial differences are largely unexplained. Folate and other methyl‐group nutrients may be related to breast carcinogenesis, but few studies have examined these associations in AA populations. We examined the associations of dietary intake of these nutrients with breast cancer risk overall, by menopausal and estrogen receptor (ER) status among 1, 582 AA (749 cases) and 1, 434 EA (744 cases) women using data from a case–control study, the Women's Circle of Health Study. Unconditional multivariable logistic regression models were used to compute odds ratios (ORs) and 95% confidence intervals (CIs) for the association of each nutrient and breast cancer risk. In AA women, inverse associations were observed for natural food folate intake among premenopausal women (fourth vs. first quartile: OR = 0.57, 95% CI, 0.33–1.00; p for trend = 0.06) and for ER‐positive tumors (fourth vs. first quartile: OR = 0.58, 95% CI, 0.36–0.93; p for trend = 0.03), whereas in EA women, a positive association was observed for intake of synthetic folate (fourth vs. first quartile: OR = 1.53, 95% CI, 1.06–2.21; p for trend = 0.03). Our findings suggest that natural food folate intake is inversely associated with breast cancer risk and that this association may vary by race, menopausal status or ER status. The finding of an increased risk observed among EA women with the highest intake of synthetic folate from fortified foods warrants further investigation.